PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KUALITAS PELAYANAN MAHASISWA (Studi pada Universitas Muslim Maros) - Ummul Chair (AkMen JURNAL ILMIAH, 2020)
The purpose of this study was to analyze the influence of organizational culture and leadership on the quality of student services at Maros Muslim University. The research was conducted at the Faculty of Economics and Business, the Faculty of Agriculture, Animal Husbandry and Forestry, and the Faculty of Teacher Training and Education at the Muslim University of Maros. Types and sources of data used are primary and secondary data. Data collection techniques are the main data collectors namely questionnaires. The population of this study is students in semester 6 (Six) 2018/2019 Academic Year in the three faculties. Student samples were taken proportionally in each of the three faculties by the proportional random sampling method. The analysis used is quantitative data analysis and multiple regression using a Likert scale. The results showed that organizational culture and leadership together had a significant effect on service quality.